Design and control of 3-DOF needle positioner for MRI-guided laser ablation of liver tumours - Franco,E; Aurisicchio,M; Ristic,M (International Journal of Biomechatronics and Biomedical Robotics, 2015)
This article presents the design and control of a pneumatic needle positioner for laser ablation of liver tumours under guidance by magnetic resonance imaging (MRI). The prototype was developed to provide accurate point-to-point remote positioning of a needle guide inside an MR scanner with the aim of evaluating the potential advantages over the manual procedure. In order to minimise alterations to the MR environment, the system employs plastic pneumatic actuators and 9 m long supply lines connecting with the control hardware located outside the magnet room. An improved sliding mode control (SMC) scheme was designed for the position control of the device. Wireless micro-coil fiducials are used for automatic registration in the reference frame of the MR scanner. The MRI-compatibility and the accuracy of the prototype are demonstrated with experiments in the MR scanner.